Evaluation of the Effect of Chitosan and Titanium Dioxide Nanoparticles Mixed with Orthodontic Primer on Shear Bond Strength: A Systematic Review and Meta-analysis - Parisa Doroudgar; Batoolalsadat Mousavi-fard; Mahdi Khadematolrasoul; Faeze Shams; Ehsan Khashabi; Zahra Mirzae Gabaran (International Journal of Scientific Research in Dental and Medical Sciences)
Background and aim: Orthodontic adhesives, commonly used to bond brackets, can significantly enhance bacterial biofilm. Nanoparticles have strong antimicrobial properties without compromising bond strength. Therefore, the aim of the present study was to evaluate the effect of chitosan and TiO2 NPs mixed with orthodontic primer on shear bond strength.Material and methods: For this systematic review and meta-analysis study, international databases such as MEDLINE (PubMed and Ovid), Web of Science, and Scopus were searched until October 2024 using keywords relevant to the study objectives. STATA/MP. v17 software was used to analyze data.Results: The present study included twelve in-vitro studies with a total sample size of 684 human premolars. The mean difference in SBS score between the 1% and 5% chitosan NPs group and control group was -1.11 MPa (MD, -1.11 MPa; 95% CI, -2.27, 0.04; p=0.16) and 5.08 MPa (MD, -5.08 MPa; 95% CI, -7.80, -2.35; p=0.09), respectively. there were no statistically significant differences after comparing the mean SBS differences between the 1% TiO2 NPs group and control group (MD, -0.43 MPa; 95% CI, -0.99, 0.12; p=0.13).Conclusions: According to the results of the present meta-analysis, 1% and 5% chitosan NPs and 1% TiO2 have potential as promising adjuncts in dental adhesive formulations, improving antimicrobial activity without compromising adhesive properties.